The Meaning of Vocation in the Leadership Journey of Women Pastors: A Narrative Analysis Approach to 20 Women Pastor Figures in Indonesia - Oki Hermawati; Fransisco Budi Hardiman; Rudy Pramono; Agustian Budi Prasetya (Pharos Journal of Theology, 2023)
This study aims to understand the meaning of vocation in the leadership journey of female pastors by conducting an in-depth analysis of the vocation stories of female pastors in order to provide an understanding of the meaning of vocations as depicted in their leadership journey. This study uses a qualitative type of research with a narrative analysis approach that focuses on analyzing the meaning of vocations to service in leadership carried out by twenty (20) female pastors who serve in various institutions in Indonesia, such as synods, churches, seminaries, Christian universities, Christian schools etc. Data processing used Nvivo software which is very reliable software in such a qualitative research undertaking. Participants emanated from various tribes, ethnicities and from various islands in Indonesia such as Java, Sumatra, East Nusa Tenggara, Bali, Sulawesi, Kalimantan, and Papua. Data collection was through the use of in-depth interviews, surveys, and observations of participants including their families, service partners and followers. The results of the data analysis will hopefully provide a comprehensive process description of the meaning of the vocation in the ministry of the female pastor's leadership which is illustrated in her unique leadership journey. The meaning of the vocation in the female pastor's leadership journey is illustrated in the diversity of vocational motivations that underlie the participants' decisions to enter the seminary. The meaning of the vocation in the female pastor's leadership journey is also illustrated in her leadership journey with the dynamics of issues of gender inequality and sociocultural views prevailing in society.